Ponte da passagem : você e cê transitando na fala de Vitória (ES) - Calmon, Elba Nusa (2010)
The present work, of sociolinguistic orientation, focuses in the use of the pronouns você, ocê, cê and te (you) spoken in the city of Vitória (ES). The data of the samples for this research are constituted of two corpora: PORTVIX (the Portuguese spoken in the city of Vitória) and CASUAL SPEECH. In order to collect the PORTVIX were selected the variants of gender, age, and level of schooling of the interviewees, whose common characteristics were to be born, to have always lived in Vitória and to have capixaba parents as well. CASUAL SPEECH, also collected from Vitória (ES) inhabitants, was constituted of two recorded conversations in which the speakers did not have any previous information about the event. In order to testify our results, we worked with quantitative analysis of speech data. For the corpora analysis, we analyzed a dependent variant according to the social variants aforementioned and also to the linguistic variant related either to syntactic aspects (subject, direct object and compliment of preposition) or to semantic aspects (generic or specific). The statistic treatment of the data was based in the GOLDVARB X computer program. Age and the gender were considered relevant by the program. Concerning age, we verified that in relation to the pronouns você e cê, a changing that shifted from você to cê was occurring. However, among those who were 15-25 years old a reverse process of this changing to the use of the pronoun você was initiated, increasing among 7-14 years old. In relation to gender, the data showed that the female tend to use the pronoun você a little more than the male do. The variant syntactic function was also selected by the program. Although there is little occurrence of data preceded by the preposition para (to/for), we noticed that this context offers more possibility for the use of the pronoun você than if it was not preceded by such a preposition. In the PORTVIX we verified that there was a positive correlation between the speech of the interviewees and the interviewers, evincing that, although sociolinguistic literature warns about the observer s paradox, emphasizing that the presence of the interviewer and of the recorder may inhibit the interviewee speech, in our research we verified a contrary situation: we testified that it was the interviewee that had influence on the interviewer s speech, since it was the interviewer that modified his/her speech when facing some situations in which the interviewee used more or less one of the variants. We compared our research to other similar works developed in other regions of Brazil and we verified that the speech of Vitória is far from that which is present in the state of Minas Gerais and it is closer to the one in Brasília. We highlight still that the use of ocê almost does not appear in the PORTVIX, in which only 0,5% of the total occurrence was registered. Yet, there is the fact that this form is rejected, according to Peres study (2008). Even in the corpus of the Casual Speech that presents very different characteristics from those of the PORTVIX, the pronoun você is also predominant. We compared the Casual Speech form to Paredes (1988) results, in corpus recorded in Rio de Janeiro, where the speakers were not conscious of the recording, we observed that in this situation the use of cê is more frequent (54,3%) than the use of você. Therefore, we noticed that in the Casual Speech, contrarily to what was found in Paredes research, the variant você was also prevalent